Analysis of postoperative colon anastomosis leakage costs - Poškus, Eligijus; Mikėnas, Saulius; Danys, Donatas (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English] Introduction. Anastomotic leakage is one of the most serious postoperative complications after colon resection operation. Concerning this complication, patients have greater chances of morbidity and mortality. In addition to the clinical complications, anastomotic leakage cause a significant financial burden to health care institution, due to additional reoperations, longer hospital length of stay, instrumental examinations and other actions, related to anastomotic leakage treatment. Materials and methods. A retrospective analysis of 39 patients, who experienced anastomotic leakage during postoperative period, was made. Data were gathered using hospital‘s electronical system and patients cases protocols. In a collaboration with Vilnius university hospital Santarų klinikos economics department, all the costs related with anastomotic leak patients treatment were counted. Anastomosis leak treatment price was compared with remuneration from National health insurance fund and also with nonleak treatment price. Results. Our study included 26 men (66,7%) and 13 women (33,3%), the mean age was 69,5±13,56 years, mean of the body mass index (BDI) – 28,34. Hospitalʼs costs average for leakage complication was greater than the remuneration for the treatment (8 373,2 ±3 709,27 Eur vs 4 097,1±1 254,66 Eur) (p < 0,001). Leakage treatment significantly cost fourfold more than nonleak treatment (8 373,2±3 709,27 Eur vs. 2 041,51±146,53 Eur), lasted longer (25,7±18,48 days vs. 7,5 days) and caused tenfold greater loss (4 275,6±2 967,84 Eur vs. 389,0±146,08 Eur). Total hospitalʼs loss during year of 2014–2016 caused due to anastomotic leakage treatment – 166 769,74 Eur. Mortality rate was 25,6%. Conclusions. Anastomosis leakage cause a great financial loss to health care institution. It is important to find the ways how to solve this problem.